Prolonged Glycation of Hen Egg White Lysozyme Generates Non Amyloidal Structures - Ghosh, Sudeshna (Public Library of Science, 2013)
Glycation causes severe damage to protein structure that could lead to amyloid formation in special cases. Here in this report, we have shown for the first time that hen egg white lysozyme (HEWL) does not undergo amyloid formation even after prolonged glycation in the presence of D-glucose, D-fructose and D-ribose. Cross-linked oligomers were formed in all the cases and ribose was found to be the most potent among the three sugars. Ribose mediated oligomers, however, exhibit Thioflavin T binding properties although microscopic images clearly show amorphous and globular morphology of the aggregates. Our study demonstrates that the structural damage of hen egg white lysozyme due to glycation generates unstructured aggregates.